Astragalus polysaccharides ameliorate epileptogenesis, cognitive impairment, and neuroinflammation in a pentylenetetrazole-induced kindling mouse model - Lu, Yuling; Lin, Minglin; Ou, Sijie; Sun, Lanfeng; Qian, Kai; Kuang, Huimin; Wu, Yuan (Frontiers in Pharmacology, 2024)
Background: Epilepsy is a prevalent neurological disease where neuroinflammation plays a significant role in epileptogenesis. Recent studies have suggested that Astragalus polysaccharides (APS) have anti-inflammatory properties, which make them a potential candidate for neuroprotection against central nervous system disease. Nevertheless, the extent of their effectiveness in treating epilepsy remains enigmatic. Therefore, our study aims to investigate the potential of APS to mitigate epileptogenesis and its comorbidities by exploring its underlying mechanism. Methods: Initially, we employed pentylenetetrazol-induced seizure mice to validate APS' effectiveness. Subsequently, we employed network pharmacology analysis to probe the possible targets and signaling pathways of APS in treating epilepsy. Ultimately, we verified the key targets and signaling pathways experimentally, predicting their mechanisms of action. Results: APS have been observed to disturb the acquisition process of kindling, leading to reduced seizure scores and a lower incidence of complete kindling. Moreover, APS has been found to improve cognitive impairments and prevent hippocampal neuronal damage during the pentylenetetrazole (PTZ)-kindling process. Subsequent network pharmacology analysis revealed that APS potentially exerted their anti-epileptic effects by targeting cytokine and toll-like receptor 4/nuclear factor kappa B (TLR4/NF-B) signaling pathways. Finally, experimental findings showed that APS efficiently inhibited the activation of astrocytes and reduced the release of pro-inflammatory mediators, such as interleukin-1β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α). In addition, APS impeded the activation of the TLR4/NF-B signaling cascade in a PTZ-induced kindling mouse model. Conclusions: The outcomes of our study suggest that APS exerts an impact on epileptogenesis and mitigates cognitive impairment by impeding neuroinflammatory processes. The mechanism underlying these observations may be attributed to the modulation of the TLR4/NF-B signaling pathway, resulting in a reduction of the release of inflammatory mediators. These findings partially agree with the predictions derived from network pharmacology analyses. As such, APS represents a potentially innovative and encouraging adjunct therapeutic option for epileptogenesis and cognitive deficit.